Harmonizing Rigor, Relevance, and Insight: A Mixed Inductive Approach for Qualitative Analysis With the Gioia Methodology and the GABEK® Method - Konrad Kressmann; Julia Mueller-Seeger (International Journal of Qualitative Methods)
Qualitative research is currently engaged in a significant debate regarding the balance between rigor and relevance within the field of organizational studies, emphasizing the need for flexible methodologies to capture the complexity of real-world practices while maintaining structured analysis processes. This paper focuses on the integration of the GABEK® Method and the Gioia Methodology, both employing inductive reasoning, Gestalt Theory, and Grounded Theory while possessing distinct characteristics that can complement each other to overcome shortcomings within one method. The study explores their application in understanding organizational culture change in professional service firms amidst the rising trend towards teleworking. Additionally, the paper highlights the absence of prescriptive rules in the Gioia methodology for conducting gestalt analysis and discusses adaptations made to incorporate GABEK® features. Through systematic data reduction and thematic analysis, the study reveals deeper meanings and interrelationships within the data, contributing to a nuanced comprehension of cultural dynamics in contemporary workplaces. Ultimately, this research underscores the importance of methodological innovation in enhancing the rigor and depth of qualitative studies, advocating for approaches that are adaptable to the evolving flexibility demands of organizational research.